Changes in soil characteristics due to the establishment of teak (Tectona grandis L.f.) plantations in pastures in Petén, Guatemala - Rodas Castellanos, Aldo F. (2006)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2006